Evaluation of physical and chemical properties of red gypsum from Terengganu, Malaysia - Nurhidayah, Mahazam; Nurul Syafiqah, Mohd Azmi (ESRSA Publications Pvt. Ltd., 2016)
Red gypsum waste generated from a local company in Malaysia were investigated in order to determine their physical and chemical properties. Red gypsum is a byproduct during the extraction of titanium dioxide from the ilmenite ores is tested for its characteristic that will be useful information for unsaturated soil and highly plasticity clay that are current scarce. Highly plasticity clay is often used in creating a barrier or backfill material. General properties such as physical and chemical properties are tested using standard laboratory procedure. Testing included the measurement of particle size analysis, cation exchange capacity and some important properties including atterberg limit, surface area and organic matter.